2020
DOI: 10.1002/prot.25958
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the specificity of Streptococcus pyogenes sortase A by loop grafting

Abstract: Sortases are a group of enzymes displayed on the cell-wall of Gram-positive bacteria. They are responsible for the attachment of virulence factors onto the peptidoglycan in a transpeptidation reaction through recognition of a pentapeptide substrate. Most housekeeping sortases recognize one specific pentapeptide motif; however, Streptococcus pyogenes sortase A (SpSrtA WT) recognizes LPETG, LPETA and LPKLG motifs. Here, we examined SpSrtA's flexible substrate specificity by investigating the role of the β7/β8 lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 37 publications
(50 reference statements)
6
16
0
Order By: Relevance
“…3A ). This result is consistent with recently published data (18). To verify that our sortases were cleaving substrates at the expected site, reactions exhibiting a normalized fluorescence value of 0.2 were independently monitored by RP-HPLC and LC-MS, which confirmed cleavage between P1 and P1’ ( Figs.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…3A ). This result is consistent with recently published data (18). To verify that our sortases were cleaving substrates at the expected site, reactions exhibiting a normalized fluorescence value of 0.2 were independently monitored by RP-HPLC and LC-MS, which confirmed cleavage between P1 and P1’ ( Figs.…”
Section: Resultssupporting
confidence: 94%
“…We find that the β7-β8 loop sequence dramatically affects both overall enzyme activity, as well as selectivity at P1’ of the CWSS. Our data is consistent with a recent publication that investigated the grafting of β7-β8 loop sequences from saSrtA and Bacillus anthracis SrtA into Streptococcus pyogenes SrtA (18). This work also suggested that W194 (saSrtA numbering) may play a role in the substrate recognition of the reported chimeras (18).…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…d) Activity enhancing mutations of SrtA from S. aureus depicted within the solution structure of the enzyme (PDB ID: 2KID). Mutations found in Chen et al (2011) [19] are displayed in orange, those found in Chen et al (2016) [20] in yellow, those from Suliman et al (2017) [21] in pink and those from Wojcik et al (2019) [22] in blue. Amino acids are labeled by type and number with respect to the S. aureus wt protein, while the corresponding mutations found in the respective screens are indicated behind the number.…”
Section: Srta-m4mentioning
confidence: 90%
“…A more recently developed Sp-SrtA chimera was engineered, focusing on altered specificity for the sortase deacylating peptide nucleophile. [22] Nucleophile recognition is largely mediated by residues of the β7-β8 loop. By grafting this region from Sa-SrtA onto Sp-SrtA, the resulting hybrid enzyme is restricted to N-Gly substrates.…”
Section: Sortase Mutants With Altered Substrate Specificitymentioning
confidence: 99%